Benefits and harms of high-dose haemodiafiltration versus high-flux haemodialysis: the comparison of high-dose haemodiafiltration with high-flux haemodialysis (CONVINCE) trial protocol. Issue 2 (5th February 2020) - Blankestijn, Peter J; Fischer, Kathrin I; Barth, Claudia; Cromm, Krister; Canaud, Bernard; Davenport, Andrew; Grobbee, Diederick E; Hegbrant, Jörgen; Roes, Kit C; Rose, Matthias; Strippoli, Giovanni FM; Vernooij, Robin WM; et al.
Abstract : Introduction: End-stage kidney disease (ESKD) is a major public health problem affecting more than 2 million people worldwide. It is one of the most severe chronic non-communicable diseases. Haemodialysis (HD) is the most common therapeutic option but is also associated with a risk of cardiovascular events, hospitalisation and suboptimal quality of life. Over the past decades, haemodiafiltration (HDF) has become available. Although high-dose HDF has shown some promising survival advantage compared to conventional HD, the evidence remains controversial. A Cochrane systematic review found, in low-quality trials, with various convective forms of dialysis, a reduction in cardiovascular, but not all-cause mortality and the effects on non-fatal cardiovascular events and hospitalisation were uncertain. In contrast, an individual patient data analysis suggested that high-dose HDF reduced both all-cause and cardiovascular mortality compared to HD. In view of these discrepant results, a definitive trial is required to determine whether high-dose HDF is preferable to high-flux HD. The comparison of high-dose HDF with high-flux HD (CONVINCE) study will assess the benefits and harms of high-dose HDF versus a conventional high-flux HD in adults with ESKD. Methods and analysis: This international, prospective, open label, randomised controlled trial aims to recruit 1800 ESKD adults treated with HD in nine European countries. Patients will be randomised 1:1 to high-dose HDF versus continuation of conventional high-flux HD. The primary outcome will be all-cause mortality at 3 years' follow-up. Secondary outcomes will include cause-specific mortality, cardiovascular events, all-cause and infection-related hospitalisations, patient-reported outcomes (eg, health-related quality of life) and cost-effectiveness. Ethics and dissemination: The CONVINCE study will address the question of benefits and harms of high-dose HDF compared to high-flux HD for kidney replacement therapy in patients with ESKD with a focus on survival, patient perspectives and cost-effectiveness. Trial registration number: Netherlands National Trial Register (NTR 7138).